(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Acute pulmonary edema is an indicator of significant pessimism and may lead to mortality in pregnant women. It is paramount to identify the at-risk patient, recognise signs of critical illness and manage these pregnancies. Estimated reported cases in pregnancy are variable, ranging from 0.08% to 1.5%. It may occur in low-risk pregnancies but should be rule out in case of dyspnea in a pregnant woman, especially in the context of pre-eclampsia. It is a life-threatening condition of which, co-existing hypertensive disorders of pregnancy, Multiple gestation contribute to maternal and perinatal complications. Early pin point of probable cause, early risk reduction strategies along with interdisciplinary approach helps in reduction of maternal morbidity and mortality. We managed a 24-year-old G2P1L1 woman at 36 weeks DCDA twin gestation with severe pre-eclampsia presenting in emergency with acute pulmonary edema and mild pulmonary hypertension.